Metabolome and Transcriptome Analysis Reveals Molecular Mechanisms of Soil Amendment (Volcanic Ash) Alleviating Salt–Alkali Stress in Melons (Cucumis melo L.) - Lina Fu; Xiaoxin Tian; Wei Wang; Chunyan Wu (Agronomy)
Salt–alkali stress can lead to a decrease in crop quality and yield, therefore, the ability to alleviate crop salt–alkali stress and elucidate its mechanism of action will be of great significance. This study investigated the effects of applying five different proportions (0%, 5%, 15%, 25%, and 35%) of volcanic ash on thin-skinned melons (Cucumis melo L.) under salt–alkali stress. Physiological test results indicated that the application of volcanic ash had a certain alleviating effect on salt–alkali stress on melons, and the effect of 35% volcanic ash was the best. Metabolome and transcriptome analysis was performed on melons grown in three different soils (rural soil, salt–alkali soil, and 35% volcanic ash treated salt–alkali soil). Notably, a total of 71 differentially expressed genes were predominantly enriched in the amino acid biosynthesis pathway. The metabolites involved in differential metabolism exhibited significant enrichment in phenylpropanoids, flavonoids, amino acids, and arginine. Intriguingly, correlation analysis between metabolomics and transcriptomics revealed significant associations among pathways such as cysteine and methionine metabolism, amino acid biosynthesis, arginine biosynthesis, alanine-aspartate-glutamate metabolism, as well as fructose–mannose metabolism. Our research elucidated the molecular mechanism of salt–alkali tolerance in thin-skinned melons, providing new references for improving salt–alkali tolerance and improving salt–alkali soil in the future.